Kinetics of Solvent Free Microwave Extraction from Amomum cardamomum: Comparison First and Second Order Models - Variyana, Yeni; Mega Arum Ariyani; Iyappateya Gelegar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The global demand for essential oil from Amomum cardamomum continues to rise due to its applications in the food, pharmaceutical, and cosmetic industries. Conventional extraction methods such as hydrodistillation face efficiency limitations due to prolonged processing times and potential thermal degradation of active compounds. This study aims to investigate the extraction kinetics of cardamom seed oil using the Solvent-Free Microwave Extraction (SFME) method and to compare the suitability of first-order and second-order kinetic models. This experimental laboratory research used cardamom seeds sourced from local farmers in Lampung. The extraction process was conducted with microwave power variations of 300, 450, and 600 W over durations ranging from 15 to 90 minutes. The oil yield was measured directly, and the data were analyzed using Microsoft Excel Solver to calculate the extraction rate constants (k₁ and k₂), saturation concentration (Ys), determination coefficient (R²), and root mean square error (RMSE). The results showed that 450 W microwave power produced the highest yield, with an R² of 0.9902 and an RMSE of 0.0851. The first-order kinetic model was found to best represent the extraction process compared to the second-order model. One advantage of this model is its simplicity in explaining how oil yield changes with varying extraction rates over time. In conclusion, SFME is an efficient and environmentally friendly green technology with strong predictive capabilities for extraction kinetics. The implications of this research provide a scientific basis for the sustainable optimization of essential oil production from tropical plants.